Factors Influencing Public Decision-Making in Oil Palm Replanting Program in Sekadau District - Hutajulu, Josua Parulian (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2023)
Considering that oil palm plants are no longer productive, replanting needs to be carried out immediately by Sekadau district farmers. For oil palm plantation farmers in Sekadau Regency, there is a dilemma in deciding to participate in this program. This research aims to find out what factors influence oil palm farmers in Sekadau Regency to carry out replanting using a quantitative descriptive approach to see the community's response to the technology provided by the government for replanting oil palm. The number of samples used in this research was 100 respondents determined by purposive sampling. The data analysis method used is logistic regression analysis. The results of this research show that the variables of land area, farmer's income level, availability of rock from the government, and age of the oil palm have a significance value of less than 0.05, which means that these variables have a strong influence on farmers' attitudes in making decisions to carry out oil palm rejuvenation activities. The percentage of decisions made by oil palm farmers to carry out replanting activities is 62.8%, where on average farmers agree to rejuvenate oil palm even though many requirements must be met.